Kommunalt koalitionsbyggande i ett nytt parlamentariskt landskap: Pragmatism i policyorienterade möjlighetsfönster (Sociologisk Forskning, 2018)
Coalition formation in a new municipal parliamentary landscape. Pragmatism in policy-related windows of opportunitiesCoalition building in Swedish municipalities has traditionally been dominated by two political blocks at the opposite sides of the ideological left–right scale (Bäck 2003; Wångmar 2006). The success of the Sweden Democrats in the last elections have challenged that pattern. Statistics on coalition formation since the 2014 election indicate that the traditional policy scale no longer dominates local government. Coalitions of parties closely situated next to each other on the left–right scale are not as common as before. Interviews with 19 leading politicians in five Swedish municipalities that formed majority coalitions, including parties on the left as well as the right block, indicate that neither the traditional left–right scale nor the GAL–TAN dimension played a decisive role in these coalition formation processes. Instead, the ability of political parties to cooperate within the coalitions and building on personal chemistry, was considered the most important factor in the coalition building process on the municipal level.
Keywords: coalition formation; policy scale; local politics; coalition cooperation; parliamentary changes